Respuesta :
Answer:
-6(7k + 11) = -49k - 66
Explanation:
We need to distribute the -6 so that we can get rid of the parentheses.
To do that, we must multiply -6 by each term that is inside the parentheses
-6 * 7k = -49k
-6 * 11 = -66
Let's put that together.
-49k - 66
So, -6(7k + 11) = -49k - 66
Answer:
= [tex]{\boxed{\rm{ -42k - 66}}}[/tex]
Explanation:
[tex]\rm{= -6(7k + 11)}[/tex]
ㅤ
[tex]\rm{= (-6) (7k + 11)}[/tex]
ㅤ
[tex]\rm{= (-6) (7k) + (-6) (11)}[/tex]
ㅤ
= [tex]{\boxed{\rm{ -42k - 66}}}[/tex]
ㅤ
Therefore, -42k - 66 is the required simplified form.